ORGANOLEPTIC TEST OF PAPAYA JAMS (Carica papaya L.) WITH DIFFERENT SUGAR CONCENTRATIONS - Grace Tessalonika; Entin Daningsih; Nurdini Mardiyyaningsih (Poltekkes Kemenkes Mataram, 2022)
Background: Papaya fruit has many benefits, is relatively abundant in West Kalimantan and has not been optimized. One of the processed foods that can raise maximum papaya utilization and extend the short shelf life of papaya is papaya jam. This study measures the effect of different sugar concentrations for acceptance using an organoleptic test on papaya jam (Carica papaya L.). Methods: The research on papaya jam used a Completely Randomized Design (CRD) with three treatments of sugar concentration (25, 45, and 65 g). Thirty untrained panelists were used as replicates. Papaya jam was evaluated using the organoleptic test to determine its acceptability of papaya jam. The assessment uses a line scalar sheet using six parameters: color, flavor, viscosity, papaya taste, sweetness level, and preference. The data of the organoleptic test were analyzed using the SAS CRD model. If there were effective treatments, then continued with the LSD test at an alpha of 0.05. This papaya jam was also analyzed for water and sugar content. Result: The results showed that the panelists favored papaya jam with a sugar concentration of 65 g. Moreover, it was chosen because it has the highest average value on color, flavor, viscosity, papaya taste, level of sweetness, and preference. Moreover, the papaya jam with a concentration of 65 g sugar resulted from it in the lowest water content and highest sugar content, according to SII year 1978. Conclusion: In the organoleptic test, papaya jam was accepted at the highest sugar concentration (65 g). Not only color, flavor viscosity, papaya taste, sweetness level and preference was significantly most elevated compared to other treatments, but papaya jam with a sugar concentration of 65 product maximum water content and minimum sugar content by SII (Indonesian Industrial Standard).